Introduction of a Statutory Registration Scheme for all Providers of Publicly Funded Legal Services In Northern Ireland : Response of the Law Society of Northern Ireland.: Response of the Law Society of Northern Ireland. ([2017]) - Law Society of Northern Ireland,
No abstract available